English as an International Language in the Icelandic Context: Teachers’ perceptions - Nevena Novakovic 1988- (2020)
In today’s world, the English language is perceived as an universal language of education, science, diplomacy, business, technology, commerce, media, tourism, and entertainment, among other areas of human activity. English is not the only language used in international communications, but it is the only language in the world whose non-native speakers outnumber the native speakers. It is precisely due to the number of non-native users of English that it receives a status of global or international language. This paper has two major purposes, that are: exploring the emerging views on the phenomenon commonly termed English as an International Language (EIL), and examining whether the effects of new ways of understanding the English language can be traced in the context of English language teaching (ELT) in Iceland. The theoretical part of the study discusses two major areas of interest for the pedagogy of English that are: multilingualism and awareness of different varieties of English; and multiculturalism and cross-cultural awareness. The empirical part of the study consists of a survey in which 30 English teachers, who teach at the compulsory and upper-secondary level in Iceland, took part. The aim was gaining insight into teachers’ perceptions and practices, firstly in relation to exposing students to different native and non-native varieties, and, secondly, in relation to incorporation of cultural elements in English classes. In their responses, majority of participants demonstrated multilingual and multicultural approach to the English language, which enables raising that kind of awareness in their students. Nonetheless, some teachers revealed certain inconsistencies between their beliefs and practices, while others expressed a more traditional pedagogical approach.